Phytochemical and antidiabetic investigations of "Tetracera Scandens" Linn - Umar, Abdulrashid (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2011)
Different parts (leaves, stems and roots) ofT. scandens L. are used in folk remedies by various indigenous peoples in different countries for the treatment of rheumatism, lowering hypertension, lowering blood pressure, inflammatory diseases, hepatitis, internal pains, urinary disorders, dysentery, child birth, sore throat, gout and diabetes related infirmities. The present work investigates the anti-diabetic activity of the polar and non-polar extracts of T. scandens L. leaves in vivo in alloxan induced diabetic and normal rats. This study was conducted in vivo and comparison was made with standard antidiabeteic drug, glibenclamide (GLBC). Glucose levels in male albino rats (Wister strain) with hyperglycemia induced by alloxan (160 mg/kg b.w.) were determined after the oral administration of the aqueous (AQ) methanolic (MEOH), butanol (BuOH), ethyl acetate (EtOAc) and dichloromethane (DCM) extracts. Four doses of AQ and MEOH extract (250, 500, 1000 and 2000 mg/kg b.w.) and a fixed dose of 500mg/kg b.w of BuOH, EtOAc and DCM extracts were evaluated. All extracts exhibited significant anti-hyperglycemic activity in alloxan induced diabetic rats, except DCM, however in normal rats no hypoglycemic activity was observed among all the extracts, when compared with both +ve & -ve controlled . The antidiabetic activity was found to be comparable to that of the effect produced by GLBC (0.25 mg/kg b.w.). The LD50 of both AQ and MEOH extracts was found to be more than 5000 mg/kg body weight and no lethal toxicity was observed within this range. This study provides scientific evidence about the leaves of T. scandens L. which possess antidiabetic agents and justifies its utility by the local herbalists to treat diabetes in Malaysia. Phytochemical investigation and chromatographic fractionation of MEOH extract of the leaves of T. scandens L. led to the isolation and structure elucidation of two new and three known flavonoids, and two known terpenoids. The occurrence of kaempferol, quercetin, isoscutellarein, 5, 7,8,3 ',5,-pentahydroxyflavone, 2, 3, 5, 6, 4' -pentahydroxy stilbene-( 4-----0-----4' ")-kaempferol-3 "-0-,8-Dglucopyranoside, stigmasterol and betullinic acid in the leaves of T. scandens L. is being reported for the first time. Keywords: Tetracera scandens Linn .. Dilleniaceae, Antidiabetic activity, Phytoconstituents